(untitled) (American Journal of Islam and Society, 2003)
This paper seeks to achieve the following objectives: to discuss the idea of unity from the Islamic and secular perspectives; to test empirically how the absence of certain universal values (virtues) in the pursued development strategies shattered unity and thereby led to the Ummah’s disintegration; to examine how the interrelationships between growth and democracy can promote unity by creating a civil society through higher human development; and to examine the Organization of the Islamic Conference’s (OIC) role in strengthening unity among diverse Muslim communities.